2007
DOI: 10.1128/jb.00585-07
|View full text |Cite
|
Sign up to set email alerts
|

SadC Reciprocally Influences Biofilm Formation and Swarming Motility via Modulation of Exopolysaccharide Production and Flagellar Function

Abstract: Pseudomonas aeruginosa has served as an important organism in the study of biofilm formation; however, we still lack an understanding of the mechanisms by which this microbe transitions to a surface lifestyle. A recent study of the early stages of biofilm formation implicated the control of flagellar reversals and production of an exopolysaccharide (EPS) as factors in the establishment of a stable association with the substratum and swarming motility. Here we present evidence that SadC (PA4332), an inner membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
329
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(355 citation statements)
references
References 59 publications
22
329
1
Order By: Relevance
“…However, a c-di-GMP component that controls this process also exists, because the individual presence of AdrA or HmsT in ⌬XII blocked motility in a manner that depended on the presence of an active GGDEF site. The latter finding is in agreement with previous studies that correlate high levels of c-di-GMP and sessility (12,(35)(36)(37)(38).…”
Section: Consequences Of Removing All Ggdef-domain Proteins In a Singlesupporting
confidence: 83%
“…However, a c-di-GMP component that controls this process also exists, because the individual presence of AdrA or HmsT in ⌬XII blocked motility in a manner that depended on the presence of an active GGDEF site. The latter finding is in agreement with previous studies that correlate high levels of c-di-GMP and sessility (12,(35)(36)(37)(38).…”
Section: Consequences Of Removing All Ggdef-domain Proteins In a Singlesupporting
confidence: 83%
“…SadC has been demonstrated to contribute to attachment. However, while inactivation of sadC by transposon mutagenesis in P. aeruginosa PA14 was shown to result in increased attachment and pellicle formation (86), deletion of sadC in the same parental strain rendered the mutant impaired in biofilm formation (104). It is likely that such inconsistencies arise from differences in parental strains or in the manner in which mutants were generated or from differences in growth conditions and experimental setup or that it may simply be a question of when over the course of the biofilm developmental process the biofilm formation capabilities were analyzed.…”
Section: Is Attachment An Indicator For Biofilm Formation?mentioning
confidence: 99%
“…In P. aeruginosa, the proteins SadB, SadC, and BifA are required for the transition from reversible to irreversible attachment by regulating several surfaceassociated behaviors, including swarming, EPS production, and modulation of flagellar reversal rates via the chemotaxis cluster IV in a c-di-GMP-dependent manner. Merritt et al (104) demonstrated that deletion of sadC, encoding an inner membrane-localized DGC, results in a hyperswarming strain defective in biofilm formation. The mutant was also deficient in polysaccharide production and displayed altered reversal patterns while swimming in high-viscosity medium, two behaviors proposed to influence biofilm formation and swarming motility.…”
Section: Let's Make It Permanent: Transition To Irreversible Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although c-di-GMP appears to be a conserved signal, the outputs it regulates are diverse and vary among different systems. These outputs include regulation of extracellular polysaccharide production (5,6), adhesin secretion and localization (7), flagellar function (6,8), and transcription of genes that direct attachment (9). Although c-di-GMP signaling has been established as a conserved modality in biofilm regulation, the specific mechanisms by which the signal is received and acted upon are largely unknown.…”
mentioning
confidence: 99%